Ostracods from Upper Ordovician (Katian) carbonate lithofacies in southwest Scotland - Mohibullah, M; Afzal, J; Williams, M; Meidla, T; Siveter, D; Zalasiewicz, J (2010)
The Ordovician Craighead Limestone Formation of southwest Scotland was formed on a carbonate platform on the eastern tropical margin of the Laurentia palaeocontinent during the early Katian (c. 456 Ma). It yields the most diverse and well-preserved ostracod fauna yet recovered from the Scottish Ordovician succession, with some 25 species divisible into two distinct marine biotopes comprising shallow lagoonal and deeper platform margin settings, respectively. The ostracods show strong biogeographic links at species-level with Sandbian and early Katian faunas of North America, including Krausella arcuata, Steusloffina cuneata, Monoceratella teres and species of Levisulculus and Platybolbina. However, many of the ostracod genera that characterize the Craighead Limestone Formation have earlier origins in the Baltica palaeocontinent, suggesting enhanced migration of species from mid- (Baltica about 30° S) to low (Laurentia) latitudes in the late Sandbian and early Katian interval. Such Baltica-origin genera include Distobolbina, Kiesowia and Platybolbina. Notable is the wide biogeographic occurrence of Steusloffina cuneata, extending from warm tropical Laurentia to cooler high-latitude Gondwana, an enormous latitudinal range for a shelf-dwelling marine species. The possible Tvaerenellidae taxon Duoarcus levigatus gen. et sp. nov. is described. Copyright © Cambridge University Press 2010.